Peningkatan Kompetensi Belajar di PKBM melalui Pelatihan Pencatatan Akuntansi Perusahaan Jasa Berbasis MYOB di Era Digitalisasi - Arie Pradina Putri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This Community Service (PkM) activity aims to improve the competency of Community Learning Center (PKBM) participants in accounting records for service companies based on the MYOB application in the digital era. The main challenges faced by participants were a lack of understanding of basic accounting concepts and limited skills in using digital accounting applications. The method used was training and mentoring with a participatory approach through lectures, discussions, demonstrations, and hands-on training. Evaluation used pre- and post-tests to measure participants' competency improvement. The results showed significant improvement, with the average score increasing from 56.4 to 82.7, or 46.6%. Furthermore, participants experienced improved skills in operating MYOB for recording transactions and preparing simple financial reports. These findings indicate that practice-based training and digital technology are effective in improving accounting literacy and technical skills. This activity also strengthened the adaptive capacity of PKBM participants to digital transformation and has the potential to become a model for sustainable service in non-formal education.